Multi-nanoprecipitate strengthened aluminium-scandium alloy for additive manufacturing - Chengwei Zang; Sheng Zhang; Mengen Zhang; Jiefei Tian; Dikai Guan; Xiao Shen; Bowen Zou; Wenwen Song; Zhiyi Zou; Pedro E.J. Rivera-Díaz-del-Castillo (Materials & Design, 2025)
Aluminium alloys, celebrated for their high strength-to-weight ratio and remarkable tensile strength in lightweight structural applications, are integral to a broad spectrum of industries. In this work, we proposed a precipitation strengthening model incorporating the competitive relationship between nucleation and growth to optimise composition, and developed an age-hardenable Al-4.2Mg-0.7Mn-1.1Sc-0.5Zr-0.6Cu-0.1Zn-0.1Fe (wt.%) alloy for laser powder bed fusion. This alloy features a hierarchically heterogeneous microstructure with a trimodal grain and nanoprecipitate distribution. It undergoes the nucleation and growth of secondary Al3X precipitates and the subsequent dissolution of the S-phase, with a significant number of T-phase observed by atom probe tomography. This combined multi-precipitate structure results in a maximum yield strength of 650 MPa displaying a high work hardening rate, making it a promising candidate for complex-shaped, high-strength and ductile components in advanced light-weight structural engineering applications. The new modelling approach to control nanoprecipitation nucleation and growth aids in realising the potential for near-net shape forming of Al alloy components.